Corpo, transnacionalismo negro e as políticas de patrimonialização: as práticas expressivas culturais negras e o circuito afrodiaspórico - Sousa, Karina Almeida de (2020)
Samba-Rock received the title of Intangiable Heritage of the city of São Paulo in 2011. This recognition dialogues with a broad movement of patrimonialization of the Black Social Clubs in the South and Southeast regions of the country. This occurred with Grêmio Recreativo e Familiar Flor de Maio, whose was recognized as material heritage of the city of São Carlos in the same year. These processes engender an important debate on nationalism and transnationalism of cultural practices and spaces articulated by the African diaspora in the Americas. Therefore, the research investigated the processes and circuits that compose the practices and spatial relations produced in the African diaspora. The investigation was based on some concepts such as contact zone, nation-state, modernity, black transnationalism, vernacular afrodiasporic circuit and black diasporic culture and African diaspora. The research has supported by participant observation, ethnographic incursion, bibliographical research and audiovisual materials (films, music and photographic records), added to interviews and data collection carried out in the state of São Paulo/BR as well as in the state of Georgia/USA from 2016 to 2019. It is concluded that, in order to understand the transits and the subjects whose expressive black cultural practices are recreated, it has become necessary to activate another element of analysis as an expressive practice: the body. It is through the inclusion of the body that the recognition of dance and music are inseparable, and the productions of the vernacular Afro diasporic circuit are expressed. In this panorama, the research was supported by a narrative proposal focused on similarities and connections, recognizing, and guiding the differences, which could be analyzed when associated with four other elements: dispersion, hybridization, creativity/improvisation and the meanings attributed to the body in the constitution of a diasporic black culture. In this way, the debate between these practices and their spaces as a constituent of a community of memory starts to gain place, tensioning, and in turn, the classical notions of the nation-state, modernity, and recognition policies (material and immaterial) as strategies (re)inscription of practices in the modern debate. Furthermore, I continue to defend the need for reflection on a political economy of black culture articulated with the dynamics of production-regulation-consumption of expressive cultural productions as one of the elements of constant (re)creation of practices in the vernacular afrodiasporic circuit.